Strengthening Preschool Teacher Competencies in Inclusive Classroom Management: A Case Study from East Kutai Regency, Indonesia - Adawiah, Rabiatul; Sukinah, Sukinah (Papanda Publisher, 2025)
Despite national policies promoting inclusive education in Indonesia, significant gaps persist between policy intentions and classroom implementation, particularly in early childhood education settings. This study examined the effectiveness of professional development programs in strengthening preschool teacher competencies for inclusive classroom management at TK Pembina, East Kutai Regency. A qualitative descriptive case study approach was employed, involving 20 preschool teachers selected through purposive sampling. Data collection occurred from January to May 2025, utilizing in-depth interviews, classroom observations, questionnaires, and document analysis. Participants were teachers who had completed inclusive education training programs and were actively implementing inclusive practices. Teachers demonstrated substantial improvements in understanding inclusive education principles and implementing Universal Design for Learning strategies. Interview data revealed enhanced confidence in managing diverse learners, with participants successfully adopting differentiated instruction approaches. Case studies illustrated transformational journeys from uncertainty to competent inclusive practice. However, persistent challenges included limited support staff, inadequate facilities, and insufficient ongoing mentoring. The findings confirm that systematic professional development can significantly enhance teacher competencies in inclusive education, supporting previous research while extending knowledge to rural Indonesian contexts. Success requires moving beyond one-time training toward sustained, practice-based learning with peer support networks. The study highlights critical needs for systemic interventions addressing resource allocation and institutional support structures alongside individual teacher development.